Elemental analysis insights into atherosclerotic calcification - L. A. Bogdanov; N. Yu. Osyaev; V. E. Markova; R. A. Mukhamadiyarov; A. R. Shabaev; A. G. Kutikhin (Сибирский научный медицинский журнал, 2021)
Background. Atherosclerosis is frequently accompanied by an extensive calcification, yet the mechanisms behind its initiation and progression remain obscure. In particular, there is unclear whether large mineral deposits grow concentrically or by merging of microcalcifications. Aim of the study was to investigate calcium phosphate maturation during atherosclerotic calcification employing an elemental analysis approach. Material and methods. We collected 20 calcified atherosclerotic plaques excised during carotid endarterectomy. After being fixed in formalin and postfixed in osmium tetroxide, plaques were dehydrated and stained in uranyl acetate with the subsequent embedding into epoxy resin, grinding, polishing, and lead citrate counterstaining. Upon the sputter coating with carbon, we visualised the plaque microanatomy by means of backscattered scanning electron microscopy. Elemental analysis was carried out using energy-dispersive X-ray spectroscopy in the backscattered mode at high vacuum and 20 kV voltage. The analysis was performed at 11 radial points within the calcium deposit and 4 control points at ascending distance from the deposit. Results. Calcium to phosphate ratio differed between the calcium deposits in distinct plaques and also within the same plaque. We found a statistically significant correlation between calcium to phosphate ratio in the center and periphery of the calcium deposit. Areas with distinct electron density had different calcium to phosphate ratio; however, there was no clear correlation between these parameters. Conclusion. Correlation of calcium to phosphate ratio in the center and periphery of the calcium deposit suggests that its maturation develops from the center to the periphery rather than by merging of neighboring calcium deposits.